Analysis of Traffic Accident Characteristics on the Pekanbaru-Bangkinang Highway KM 20-60, Kampar Regency - Adeswastoto, Hanantatur; Febryanto; Febrianty, Nanda Lelis; Saputra, Muhammad Azlan; Yeti, Salsa Bilah (Journal of Engineering Science and Technology Management, 2025)
Based on the Kampar Police traffic accident report data, on the Pekanbaru - Bangkinang KM 20 - 60 highway section, there have been many cases of traffic accidents that have caused material losses, minor injuries, serious injuries, and death. This study aims to determine and identify the causal factors and characteristics of traffic accidents. The method used in this research is descriptive qualitative method based on primary data from direct observation and secondary data obtained from relevant agencies, namely the Kampar Traffic Police related to traffic accidents. The results of the analysis show that on the Pekanbaru - Bangkinang KM 20 - 60 highway section can be identified The results of the analysis according to the 2018 - 2022 data show that based on the time of occurrence the most frequent accident is at 14.00 - 16.00 WIB with 50 accidents. Based on the vehicle involved, it is known that the most frequent accidents are caused by motorbikes - motorbikes as many as 76 incidents. the number of accident victims is 320 people where 65 people died, 67 people were seriously injured, 188 people were slightly injured. Most accident involvement is teenagers aged 15-20 years. This shows that at that age there is still a lack of awareness of driving knowledge.